Ensuring and Restoring Balance on Access to Controlled Substances for Medical and Scientific Purposes: Joint Statement from Palliative Care Organizations. (3rd July 2018) - Pettus, Katherine; De Lima, Liliana; Maurer, Martha; Husain, Asra; Connor, Stephen; Torode, Julie; Ling, Julie; Downing, Julia; Rajagopal, M. R.; Radbruch, Lukas; Pastrana, Tania; Luyirika, Emmanuel B.; et al.
Abstract: The central principle of "balance" represents the dual obligation of governments to establish a system of control that ensures the adequate availability of controlled substances for medical and scientific purposes while simultaneously preventing their nonmedical use, diversion, and trafficking, two primary goals of the international control system. On the one hand, although strong opioids, including morphine, are absolutely necessary for the relief of severe pain, legitimate access to opioids for pain treatment and palliative care is lacking in the majority of the world's countries. On the other hand, in a few high-income countries with higher consumption of prescription opioids, diversion and nonmedical use are increasingly prevalent. This report presents examples of unbalanced systems and a joint statement from global and regional palliative care organizations to promote development of balanced systems for optimal public health outcomes. Although nonmedical use of controlled substances poses a risk to society, the system of control is not intended to be a barrier to their availability for medical and scientific purposes, nor to interfere in their legitimate medical use for patient care. As representatives of palliative care organizations, we urge heads of state to act and to take measures to ensure and restore balanced systems in their countries and call on public health leaders and regulators to work together.